Forecasting market crashes: further international evidence - Terhi Jokipii (Bank of Finland, 2006)
This paper studies the extent to which market crashes are predictable for a set of six countries, focusing in particular on possible differences between transition economies (The Czech Republic, Hungary and Poland) and mature markets (UK, US and EU). We estimate a set of individual country and pooled specifications to find that market crashes, in the broader sense, are predictable for all countries analysed.We additionally investigate the role that investor heterogeneity, proxied by trading volume, plays in this predictability and find some varying results between countries.For the Central and Eastern European Countries (CE3), an increase in trading volume relative to trend appears to have great predictive power, a result that is supportive of the theory of investor heterogeneity outlined in the relevant background studies. For the more mature markets (G5), on the other hand, market crashes appear more likely to follow a period of increased stock prices and returns, a result fitting a number of traditional theories, in particular the stochastic bubble model.Further analysis, allowing for time-varying coefficients, confirms the volume-crash relationship for the CE3 and provides preliminary evidence that macro news releases may additionally contribute to the predictability of market crashes.
URN:NBN:fi:bof-20140807321
Keywords: C14; G12; G15; 330; aggregate market returns; skewness; trading volume; market crash